A novel serum protein purification technique combined with surface-enhanced Raman spectroscopy for liver cancer detection. Issue 2 (7th February 2021) - Tang, Shuzhen; Gao, Siqi; Xu, Jianshu; Zheng, Mengmeng; Huang, Yimei; Yu, Yun; Lin, Juqiang
Abstract: In this study, silver nanoparticles-based surface-enhanced Raman spectroscopy combined with a serum protein purification method was employed to screen liver tumors. The cellulose acetate membrane was used to separate proteins from human serum, and then the purified serum proteins were mixed with silver nanoparticles for surface-enhanced Raman spectroscopy detection. High-quality spectra were recorded from serum protein samples belonging to 45 healthy volunteers and 42 liver cancer patients, and the diagnostic sensitivity and specificity of liver cancer were 90.5% and 95.6%, respectively, indicating that this method has great application potential for the detection and screening of liver cancer.